Analisis Perkembangan LKNB Syariah dalam Meningkatkan Sustainable Development Goals di Indonesia - Muhammad Fadil Zuhri; Mutiara Liza; Wildan Syahputra; Enika Diana Batubara (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThis research discusses the development of the role of sharia LKNB in improving Sustainable Development Goals in Indonesia. The research method used is descriptive qualitative. The result is that sharia LKNB in Indonesia has not increased because one of the sharia LKNB products, namely pension funds and insurance, has not increased the achievement of poverty alleviation and gender equality as the goals of the SDGs in Indonesia. This research is expected to be a trigger for both the government and the private sector to make sukuk as financing for SDGs-based programs. In addition, to invite the general public to be able to compress in participating in developing the State and be active in achieving the SDGs goals.Keywoards: Sharia LKNB, Sustainable Development Goals